2021
DOI: 10.3390/ma14051266
|View full text |Cite
|
Sign up to set email alerts
|

Performance-Guided Design of Permeable Asphalt Concrete with Modified Asphalt Binder Using Crumb Rubber and SBS Modifier for Sponge Cities

Abstract: The construction of sponge city is a major green innovation to implement the concept of sustainable development. In this study, the road performance of permeable asphalt concrete (PAC), which displays pronounced water permeability and noise reduction that are favorable for sponge cities, has been improved with a two-fold modification using styrene–butadiene–styrene (SBS) and crumb rubber (CR). Four percent SBS and three different ratios (10%, 15%, and 20%) of CR have been used to modify the virgin asphalt bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In fact, a healthy built environment must not only pay attention to these three aspects but should also consider the air impacts, Life Cycle Assessment (LAC), GHG emission and so on. These will be researched in the next step [73,74].…”
Section: Limitationsmentioning
confidence: 99%
“…In fact, a healthy built environment must not only pay attention to these three aspects but should also consider the air impacts, Life Cycle Assessment (LAC), GHG emission and so on. These will be researched in the next step [73,74].…”
Section: Limitationsmentioning
confidence: 99%
“…The porous mixture's durability enhancement and fatigue resistance improvements can be achieved using modified asphalts [23]. Some authors have confirmed the porous asphalt mixtures' mechanical performance improvements through the introduction of fibres [25][26][27] or fatty acid amides [28] and by using modified asphalts, such as epoxy [29], polyurethane [30], rubber from waste tires [31], and styrene butadiene styrene-SBS [32][33][34].…”
Section: Introductionmentioning
confidence: 96%
“…However, the cost of SBS-modified asphalt is relatively high, so the proportion of SBS must be controlled when preparing sealant in order to reduce the engineering cost, while at the same time guaranteeing good service performance (such as high-temperature properties) [31]. Thus, some researchers have thought of combining SBS and CR to modify asphalt materials so as to improve their high-temperature resistance while reducing their cost [32].…”
Section: Introductionmentioning
confidence: 99%